Легкие горы: [для среднего школьного возраста : 12+] / Тамара Михеева - Михеева Тамара (Net. Na. Carte, 2013)
Экземпляры: ф.2 (20140623) / Инвентарный номер: 55923 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: М 69 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44^VLBC/PL